Nutritional Status and Infant and Young Child Feeding (IYCF) Practices among Buhid Mangyan Tribe, Occidental Mindoro Philippines - Jr., Artemio M. Gonzales; Salvador, Marciel N. (International Journal of Child Health and Nutrition, 2020)
Nutritionally adequate and safe complementary feeding starting from the age of 6 months up to 59 months is one of the effective intervention to reduce infant and child morbidity and malnutrition. This study aims to determine the nutritional status of children ages 6-59 months and their caregiver’s infant and young child feeding (IYCF) practices of the Buhid community in Rizal, Occidental Mindoro. The design used in this study was a descriptive cross-sectional carried out between December 2016-February 2017. A survey questionnaire was utilized as an instrument in this study. It includes an anthropometric survey of 6-59 months old and infant and young child feeding practices using WHO and UNICEF IYCF indicators. Vaccination, vitamin A supplementation and deworming coverage were also measured. Findings revealed a prevalence of global acute malnutrition (GAM) at a critical level. There is a low but significant prevalence of stunting and underweight among children. There is a good infant and young feeding practice in the community except for the minimum acceptable diet during complementary feeding. Lastly, there is low BCG and measles vaccination coverage in the community that could be a threat to the impending disease outbreak.